Genomics assisted breeding: The need and current perspective for rice improvement in India - Katara, Jawahar Lal; C, Parameswaran; BN, Devanna; Verma, Ram Lakhan; C, Anil Kumar; Patra, B C; Samantaray, Sanghamitra (ORYZA-An International Journal of Rice, 2021)
With the fast increase of human population and reduction in land areas under cultivation, it is essential to breedÂ rice varieties with higher yield potential and tolerance to multiple stresses using modern breeding technologies.Â Till date, a large number of rice varieties and rice hybrids have been developed in India for different ecologies.Â However, average rice production in India is 2600 kg/hectare. Since rice is the staple food in India and grownÂ in 43.86 million hectare, the present production and productivity are not sufficient enough to feed the increasingÂ population. Therefore, it is required to develop high yielding rice varieties to feed the growing population.Â However, HYVs are usually amenable to various biotic and abiotic stresses for which there is a great yield loss.Â Besides, there is no significant increase in yield though a number of high yielding rice varieties have beenÂ developed through conventional breeding. Thus, higher genetic gain in rice is required to combat the existingÂ situation which is only possible through advanced breeding approaches such as genomic selection, forwardÂ breeding, haplotype-based precision breeding along with genomic tools such as Next-Generation SequencingÂ (NGS) technology. This review addresses the current progress made in advanced genomic-assisted breedingÂ and need of modern breeding technologies for rice improvement.